The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1080/02642069.2010.529437
|View full text |Cite
|
Sign up to set email alerts
|

The impact of banks and non-bank financial institutions on economic growth

Abstract: Empirical studies examining the relationship between financial sector development and economic growth without including non-bank financial institutions (NBFIs) will likely generate biased empirical results. This study provides evidence that NBFIs can have a statistically significant negative impact on economic growth using cross-country data for both emerging and advanced countries. This finding suggests that these non-bank institutions, often loosely regulated, may introduce an excessive level of risk into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
(32 reference statements)
1
31
0
1
Order By: Relevance
“…Investigations into the relationship between finance and economic growth have reported conflicting outcomes. Whereas studies such as Jalil and Feridun [29], Tran [30], Waqabaca [31], Levine et al [32] find a positive relationship between finance and growth, studies such as Adusei [33,34], Hye and Islam [35], Adusei [36], Liang and Reichert [37] and Ram [38] report a negative relationship between the two. Few studies have reported an insignificant relationship between finance and growth [39,40].…”
Section: Other Determinants Of Economic Growthmentioning
confidence: 99%
“…Investigations into the relationship between finance and economic growth have reported conflicting outcomes. Whereas studies such as Jalil and Feridun [29], Tran [30], Waqabaca [31], Levine et al [32] find a positive relationship between finance and growth, studies such as Adusei [33,34], Hye and Islam [35], Adusei [36], Liang and Reichert [37] and Ram [38] report a negative relationship between the two. Few studies have reported an insignificant relationship between finance and growth [39,40].…”
Section: Other Determinants Of Economic Growthmentioning
confidence: 99%
“…The research work of Liang and Reichert (2012) found a negative relationship between non-bank financial institution and economic growth for both developed and developing countries. It believed that the negative results for the developed countries are not justified by the trends but might reflect the lack of adequate regulatory supervision (Liang & Reichert, 2012) and unacceptable speculative management style of the large non-bank financial institutions which endangered customers' wealth and the financial system. The recent value destruction from the very systemically important non-bank financial institutions might explain this exposition.…”
Section: Policies Financial Structures and Non Bank Financial Institmentioning
confidence: 99%
“…Liang and Reichert (2012) suggest that at low level of economic growth, the relationship is likely to be demand following economic development because financial intermediation services are typically low at that level but picks up as development accelerates. At higher levels of development, financial intermediation role assumes a leading role in resource allocation and risk diversification (Liang & Reichert, 2007).…”
Section: Finance and Financial Developmentmentioning
confidence: 99%
See 2 more Smart Citations